Are nematodes costly to fig tree–fig wasp mutualists?. Issue 12 (6th December 2019) - Shi, Rong‐Rong; Miao, Bai‐Ge; Segar, Simon T.; Zeng, Yongsan; Wang, Bo; Peng, Yan‐Qiong
Abstract: Most mutualisms are exploited by parasites, which must strike an evolutionary balance between virulence and long‐term persistence. Fig‐associated nematodes, living inside figs and dispersed by fig wasps, are thought to be exploiters of the fig–fig wasp mutualism. The life history of nematodes is synchronized with the fig development and adapted to particular developmental characteristics of figs. We expect host breeding systems (monoecious vs. gynodioecious figs) and seasonality to be central to this adaptation. However, the details of the adaptation are largely unknown. Here, we conducted the first field surveys on the prevalence of nematodes from monoecious Ficus microcarpa L.f. (Moraceae), gynodioecious Ficus hispida L.f., and their pollinating fig wasps in two seasons and two developmental stages of figs in Xishuangbanna, China. We followed this up by quantifying the effects of nematodes on fitness‐related traits on fig wasps (e.g., egg loads, pollen grains, and longevity) and fig trees (seed production) in gynodioecious F. hispida . The magnitude of nematode infection was compared between pre‐ and post‐dispersal pollinators to quantify the probability of nematodes being transported to new hosts. Our results showed that Ficophagus microcarpus (Nematoda: Aphelenchoididae) was the only nematode in F. microcarpa . In F. hispida, Martininema guangzhouensis (Nematoda: Aphelenchoididae) was the dominant nematode species, whereas Ficophagus centerae was rare. For both species of Ficus, rainy season and inter‐floral figs had higher rates of nematode infection than the dry‐hot season and receptive figs. Nematodes did not affect the number of pollen grains or egg loads of female wasps. We did not detect a correlation between seed production and nematode infection. However, carrying nematodes reduced the lifespan and dispersal ability of pollinator wasps, indicating higher rates of post‐emergence mortality in infected fig wasps. Severely infected fig wasps were likely 'filtered out', preventing the overexploitation of figs by wasps and stabilizing the interaction over evolutionary time. Abstract : Most mutualisms are exploited by parasites, which must strike an evolutionary balance between virulence and long‐term persistence. Fig parasitic nematodes are parasites of the fig–fig wasp mutualism – they consume fig tissue and rely on pollinating wasps for dispersal. Carrying nematodes reduced the lifespan and dispersal ability of pollinator wasps. Network thinking is required to treat the syconium as a whole, incorporating the interactions among fig, pollinating fig wasp, multispecies of non‐pollinating fig wasps, nematodes, fungi, and even bacteria.